Implication of Porphyromonas gingivalis in colitis and homeostasis of intestinal epithelium - Seo, Yoojin; Oh, Su-Jeong; Ahn, Ji-Su; Shin, Ye Young; Yang, Ji Won; Kim, Hyung-Sik (Laboratory animal research, 2019)
Emerging evidences have reported that periodontitis can be a risk factor for the pathogenesis of various systemic diseases. Porphyromonas gingivalis ( Pg ), one of the crucial pathogens in chronic periodontitis, has been spotlighted as a potential cause for the promotion and acceleration of periodontitis-associated systemic disorders. To investigate the association between Pg and intestinal disease or homeostasis, we treated Pg -derived lipopolysaccharide (LPS) in murine colitis model or intestinal organoid, respectively. Pg -derived LPS ( Pg LPS) was administrated into chemically induced murine colitis model and disease symptoms were monitored compared with the infusion of LPS derived from E. coli ( Ec LPS). Organoids isolated and cultured from mouse small intestine were treated with Pg or Ec LPS and further analyzed for the generation and composition of organoids. In vivo observations demonstrated that both Pg and Ec LPS exerted slight protective effects against murine colitis. Pg LPS did not affect the generation and growth of intestinal epithelial organoids. Among subtypes of epithelial cells, markers for stem cells, goblet cells or Paneth cells were changed in response to Pg LPS. Taken together, these results indicate that Pg LPS leads to partial improvement in colitis and that its treatment does not significantly affect the self-organization of intestinal organoids but may regulate the epithelial composition.